Castro, Anita (audio interview #6 of 6) - Castro, Anita (b. 1908? - d. unknown); Berger Gluck, Sherna, interviewer
INTERVIEW DESCRIPTION - This is the sixth and final interview with Anita Castro, conducted in her home. She became very emotional when speaking about certain aspects of her life, particularly her medical history and the fact that she was unable to have more children. In addition to the difficulties in fully understanding her due to her speaking style, there are segments of the interview where there is background noise and other places where the recording is interrupted. TOPICS - her medical history; her divorce and being shot by a Mexican man in Montana who wanted to marry her; the formation of the Mandolin Club in the union; and her efforts to start a ceramics class for union members;the formation of various classes and activities in the union; gender discrimination; ethnic discrimination and union domination by Jews; retirement; and the Retirees Club; 8/17/1976